Model Pembelajaran Tradisional dan Kontemporer dalam Pendidikan Agama Islam - Tiara Dwi Putri; Zumirrahilza Haq; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2025)
Islamic religious education plays an important role in shaping individual character and morality. In this context, the learning model used has a significant impact on learning effectiveness. This article discusses the comparison between traditional and contemporary learning models in Islamic religious education. Traditional models, which are often didactic and teacher-centered, tend to emphasize memorization and repetition, whereas contemporary models emphasize interactive, collaborative, and problem-based approaches. This research uses qualitative methods with case study analysis in several Islamic educational institutions. The results show that contemporary learning models increase student engagement, understanding of concepts, and ability to apply religious values in everyday life. Meanwhile, traditional models still have relevance in providing a strong knowledge base. This article recommends the integration of both models to create a more holistic and effective learning environment, where students not only memorize religious teachings but are also able to apply them in a modern context. It is hoped that these findings can contribute to the development of an Islamic religious education curriculum that is more adaptive and relevant to the needs of the times.